Texas lizards : a field guide - Hibbitts, Troy D., 1970- (Texas natural history guides., 2015)
"Texas offers the opportunity to observe lizard diversity like no other part of the country," writes Laurie J. Vitt in the foreword to Texas Lizards. From the moist eastern Piney Woods to the western deserts, lizards can be found in every part of Texas. The state has forty-five native and six naturalized species of lizards, almost half of the 115 species that live in the continental United States. Yet Texas lizards have not received full coverage in regional field guides, and no other guide dedicated solely to the state?s lizards has ever been published. Texas Lizards is a complete identification guide to all fifty-one native and established exotic lizard species. It offers detailed species accounts, range maps, and excellent color photographs (including regional, gender, and age variations for many species) to aid field identification. The authors, two of the state?s most knowledgeable herpetologists, open the book with a broad overview of lizard natural history, conservation biology, observation, and captive maintenance before providing a key to Texas lizards and accounts of the various lizard families and species. Appendices list species of questionable occurrence in Texas and nonestablished exotic species. Informational resources on Texas lizards, a map of Texas counties, a glossary, a bibliography, and indexes of common and scientific names round out the volume.